Periprosthetic Fractures Following Total Knee Arthroplasty - Yoo, Jae Doo (Knee Surg Relat Res, 2015)
Periprosthetic fractures after total knee arthroplasty may occur in any part of the femur, tibia and patella, and the most common pattern involves the supracondylar area of the distal femur. Supracondylar periprosthetic fractures frequently occur above a well-fixed prosthesis, and risk factors include anterior femoral cortical notching and use of the rotational constrained implant. Periprosthetic tibial fractures are frequently associated with loose components and malalignment or malposition of implants. Fractures of the patella are much less common and associated with rheumatoid arthritis, use of steroid, osteonecrosis and malalignment of implants. Most patients with periprosthetic fractures around the knee are the elderly with poor bone quality. There are many difficulties and increased risk of nonunion after treatment because reduction and internal fixation is interfered with by preexisting prosthesis and bone cement. Additionally, previous soft tissue injury is another disadvantageous condition for bone healing. Many authors reported good clinical outcomes after non-operative treatment of undisplaced or minimally displaced periprosthetic fractures; however, open reduction or revision arthroplasty was required in displaced fractures or fractures with unstable prosthesis. Periprosthetic fractures around the knee should be prevented by appropriate technique during total knee arthroplasty. Nevertheless, if a periprosthetic fracture occurs, an appropriate treatment method should be selected considering the stability of the prosthesis, displacement of fracture and bone quality.